SME Policies and State Structures in Argentina (2003-2015): Opaque Links and Unexplored Shadows - Seiler, Cristhian Rubén; Fernández, Víctor Ramiro (Revista del CLAD Reforma y Democracia, 2017)
This work analyzes the way in which the implementation of SME policies and programs (SPP) coming from and/or financed by international financing agencies (particularly IDB and UNDP) promotes neoliberal characteristics in SME structure and involvement that weakening the strategic character of the State in development. In order to do so, by acknowledging the disputed nature and the institutional fragility of the State in Latin America, the document is interested in noting that the implemented SPPs were constituted in technologies of power with capacity not only to make feasible and deepen the organizational fragmentation of SME state structures and competition between them, but also to disseminate ideas and conceptual frameworks that shaped a state involvement that prioritizes global insertion over a national development project. The research focused its analysis on the Small and Medium Enterprise and Regional Development Secretariat and on two of the most important SPPs (Business Reconversion Program/Program to Support Credit and Competitiveness, and the Local Productive Systems Program) implemented in Argentina (2003-2015).